Periodontal regeneration in swine after cell injection and cell sheet transplantation of human dental pulp stem cells following good manufacturing practice. Issue 1 (December 2016) - Hu, Jingchao; Cao, Yu; Xie, Yilin; Wang, Hua; Fan, Zhipeng; Wang, Jinsong; Zhang, Chunmei; Wang, Jinsong; Wu, Chu-tse; Wang, Songlin
Abstract Background Periodontitis, one of the most prevalent infectious diseases in humans, results in the destruction of tooth-supporting tissues. The purpose of the present study is to evaluate the effect of cell injection and cell sheet transplantation on periodontal regeneration in a swine model. Methods In the present study, human dental pulp stem cells (hDPSCs) were transplanted into a swine model for periodontal regeneration. Twelve miniature pigs were used to generate periodontitis with bone defects of 5 mm in width, 7 mm in length, and 3 mm in depth. hDPSCs were obtained for bone regeneration using cell injection or cell sheet transplantation. After 12 weeks, clinical, radiological, and histological assessments of regenerated periodontal tissues were performed to compare periodontal regeneration treated with xenogeneic cell injection and cell sheet implantation. Results Our study showed that translating hDPSCs into this large animal model could significantly improve periodontal bone regeneration and soft tissue healing. After 12 weeks, both the hDPSC sheet treatment and hDPSC injection significantly improved periodontal tissue healing clinically in comparison with the control group. The volume of regenerative bone in the hDPSC sheet group (52.7 ± 4.1 mm3 ) was significantly larger than in the hDPSC injection group (32.4 ± 5.1 mm3 ) (P < 0.05). The percentage of bone in the periodontium in the hDPSC injection group was 12.8 ± 4.4 %, while it was 17.4 ± 5.3 % in the hDPSC sheet group (P < 0.05). Conclusion Both hDPSC injection and cell sheet transplantation significantly regenerated periodontal bone in swine. The hDPSC sheet had more bone regeneration capacity compared with hDPSC injection.